2021
DOI: 10.34172/ipp.2021.28
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivitis and other ocular manifestation following COVID-19; updated information about transmission of COVID-19 by eye

Abstract: Coronavirus disease 2019 (COVID-19) was reported in Wuhan, in late December 2019 and was became a pandemic health problem worldwide. In this review, the current evidence related to the ocular transmission of SARS-CoV-2 and its common manifestations was studied. According to this review, 7% to 69.4% of patients had at least an ocular symptom following COVID-19. Ocular symptom are bilateral or unilateral conjunctivitis, increased secretion, eye itching and foreign body sensation, epiphora, dry eye, conjunctival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…COVID-19 was distributed worldwide and showed various symptoms, including lung involvement, liver and kidney damage, and conjunctivitis. COIVD-19 is considered a disease with multi-organ failure ability [2][3][4][5][6][7]. After declaring the Pandemic by WHO, researches were done further to find remedy and vaccines [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 was distributed worldwide and showed various symptoms, including lung involvement, liver and kidney damage, and conjunctivitis. COIVD-19 is considered a disease with multi-organ failure ability [2][3][4][5][6][7]. After declaring the Pandemic by WHO, researches were done further to find remedy and vaccines [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…2 associated with mortality in patients with COVID-19 and hypoxia of the lower extremities has been diagnosed as the cause of death without lung involvement (4)(5)(6). Today, it is known that COVID-19 causes multi-organ failure including conjunctivitis, kidney, liver, olfactory system and even mental status (7)(8)(9)(10)(11). Identifying the patients at risk of death from COVID-19 is one of the fundamental challenges for clinical physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important role of stress in pregnancy, it is essential to have psychological interventions targeting women with previous miscarriages or stillbirths to improve maternal and neonatal outcomes [20] . The research found that the COVID-19 virus can involve all organs like kidneys, lungs, eyes, and skin, and even can result in depression and other psychological problems [21][22][23][24][25][26] . Pregnant women are more vulnerable compared to others in front of infections and their consequences so the psychological impact of COVID-19 must be considered in the interpretation of decisions during the COVID-19 pandemic [27] .…”
Section: Introductionmentioning
confidence: 99%